Evaluation of a Sepsis Alert in the Pediatric Acute Care Setting - Gibbs, Karen DiValerio; Shi, Yan; Sanders, Nicole; Bodnar, Anthony; Brown, Terri; Shah, Mona D.; Hess, Lauren M. (Applied Clinical Informatics, 2021)
Background Severe sepsis can cause significant morbidity and mortality in pediatric patients. Early recognition and treatment are vital to improving patient outcomes.Objective The study aimed to evaluate the impact of a best practice alert in improving recognition of sepsis and timely treatment to improve mortality in the pediatric acute care setting.Methods A multidisciplinary team adapted a sepsis alert from the emergency room setting to facilitate identification of sepsis in acute care pediatric inpatient areas. The sepsis alert included clinical decision support to aid in timely treatment, prompting the use of intravenous fluid boluses, and antibiotic administration. We compared sepsis-attributable mortality, time to fluid and antibiotic administration, proportion of patients who required transfer to a higher level of care, and antibiotic days for the year prior to the sepsis alert (2017) to the postimplementation phase (2019).Results We had 79 cases of severe sepsis in 2017 and 154 cases in 2019. Of these, we found an absolute reduction in both 3-day sepsis-attributable mortality (2.53 vs. 0%) and 30-day mortality (3.8 vs. 1.3%) when comparing the pre- and postintervention groups. Though our analysis was underpowered due to small sample size, we also identified reductions in median time to fluid and antibiotic administration, proportion of patients who were transferred to the intensive care unit, and no observable increase in antibiotic days.Conclusion Electronic sepsis alerts may assist in improving recognition of sepsis and support timely antibiotic and fluid administration in pediatric acute care settings.
Keywords: pediatric sepsis; acute care; quality improvement